PENGARUH COVID-19 TERHADAP EKONOMI DALAM TINJAUAN HUKUM ISLAM - Syukur Yana Mardiana; Wanda Siti Cahyani (AL-INTIFA, 2023)
Islam as rahmatan lil alamin which includes all aspects of law including economic law which became known as Islamic economics. The economy is a basic need in human life to be able to live and develop in daily life, without the economy, the activities and processes of human life will be disrupted, including the situation and conditions of the co-19 pandemic. The impact of Covid-19 will be more felt on the economy of middle-low society. The experts of Islamic Law are of the view that in general the fulfillment of needs is a shared community obligation so that no one found still feels the loss of basic necessities of life. The solution to the co-19 impact that can be done is by channeling cash direct assistance from zakat, infaq and alms, both from zakat collection units and from the community. Specifically for zakat being paid, its distribution can be focused on the poor who are directly affected by Covid-19, as one who has the right to receive it (mustahik).